2007
DOI: 10.1093/jaoac/90.4.1180
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Diffuse Reflectance Fourier Transform Infrared Spectroscopic Determination of Sulfur Dioxide in Ambient Air Using Potassium Tetrachloromercurate as the Absorbing Reagent

Abstract: This paper presents development of a simple, rapid, and precise analytical method for determination of sulfur dioxide in ambient air by a gas to solid-phase conversion method. Sulfur dioxide is determined in the form of sulfite (SO32) because the absorbing reagent, potassium tetrachloromercurate (TCM), used in this method absorbs sulfur dioxide from the atmosphere in the form of sulfite. Determination of submicrogram levels of sulfur dioxide was based on the selection of a quantitative analytical peak at 495 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Verma et al . [, , ] found high loadings of PM 2.5 (average 239 µg m −3 ) and PM 2.5‐10 aerosols (average 245 µg m −3 ), and gaseous pollutants such as SO 2 (average 95.2 µg m −3 ) and NO 2 (average 115 µg m −3 ) in the atmosphere of Raipur. A cluster of coal‐based industries and growing vehicular population as well as use of firewood and cow dung for domestic cooking are considered as emitters of considerable amount of aerosol particles in Raipur.…”
Section: Introductionmentioning
confidence: 99%
“…Verma et al . [, , ] found high loadings of PM 2.5 (average 239 µg m −3 ) and PM 2.5‐10 aerosols (average 245 µg m −3 ), and gaseous pollutants such as SO 2 (average 95.2 µg m −3 ) and NO 2 (average 115 µg m −3 ) in the atmosphere of Raipur. A cluster of coal‐based industries and growing vehicular population as well as use of firewood and cow dung for domestic cooking are considered as emitters of considerable amount of aerosol particles in Raipur.…”
Section: Introductionmentioning
confidence: 99%
“…Biomass burning and combustion of biofuels are identified as the major sources of OAs in eastern central India (Giri et al, 2013;Nirmalkar et al, 2015;Deshmukh et al, 2016). Verma et al (2007Verma et al ( , 2008Verma et al ( , 2010 found high loadings of fine mode aerosols (avg. 239 µg m -3 ) and coarse mode aerosols (avg.…”
Section: Introductionmentioning
confidence: 99%